FORMATION OF CREATIVE ABILITIES OF PRIMARY SCHOOL STUDENTS - D. A. Kulboyeva; M. B. Tursunova (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, the formation of creative abilities of primary school students. Also, to organize technology lessons based on the STEAM approach and to give students an understanding on this basis.